2015
DOI: 10.1183/13993003.01454-2015
|View full text |Cite
|
Sign up to set email alerts
|

Low paediatric tuberculosis case detection rate in Southern Mozambique

Abstract: Two core indicators adopted for evaluating tuberculosis (TB) control programmes are treatment outcome and case detection rate (CDR). While the former is easy to report, the CDR can only be estimated (calculated as notifications of new and relapse cases divided by estimated incidence). According to the World Health Organization (WHO), Mozambique has one of the lowest CDRs among the high TB burden countries (HBCs), with 37% in 2013 [1]. In children, calculating CDR is even more challenging, given the difficulty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…TB cases were classified according to the NIH classification [16]. This study showed that the incidence rate of TB among children aged less than 3 years was 470/100,000person-years, with a low estimated case detection rate of 40.8% (95% CI 36.6–45.1%)[6,15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TB cases were classified according to the NIH classification [16]. This study showed that the incidence rate of TB among children aged less than 3 years was 470/100,000person-years, with a low estimated case detection rate of 40.8% (95% CI 36.6–45.1%)[6,15]. …”
Section: Methodsmentioning
confidence: 99%
“…However, underdetection is common [6], partially due to the inherent difficulties in obtaining respiratory samples in children, coupled to the paucibacillary nature of TB in this age group [5]. An additional layer of complexity is posed by the fact that NTM lung disease and tuberculosis (TB) have overlapping clinical and radiological manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…Mozambique with a population of 27 million people in 2014, has low case detection rate, below 50%[17], the estimated TB incidence is around 551 cases per 100,000 population; of these cases, an estimated 58% are HIV co-infected [18]. By 2014, 24 Xpert machines were operating in the country [1].…”
Section: Introductionmentioning
confidence: 99%
“…25 This estimate was confirmed in a recent study conducted in Southern Mozambique where the TB case detection rate in children < 3 years of age was considered to be 40.8%. 36 The greatest case detection failure occurs in young children, and in a setting with poor epidemic control and little use of preventive therapy, children < 5 years are expected to account for at least half of all pediatric cases. The potential reporting gap of child TB cases is also emphasized by post-mortem examinations and by the yield of intensified case-finding (ICF) initiatives.…”
Section: Pediatric Tuberculosismentioning
confidence: 99%